Analisis Prilaku Masyarakat Terhadap Pandemi Covid-19 Pada Masa New Normal - Rosmeri Bukit (Jurnal Kesmas Prima Indonesia, 2022)
The World Health Organization (WHO) set on March 11, 2020, as a global pandemic status for the 2019 co rona virus disease or what is also called the corona virus disease 2019 (COVID-19), because all citizens of the world have the potential to be infected with the COVID-19 disease. The case of COVID-19 has not shown a decrease and even tends to increase, so the community and government must carry out life habits in all sectors in the midst of the COVID-19 (The New normal). The purpose of this research is to find out the results of the analysis of community behavior consisting of knowledge, attitudes and behavior) of the community. against COVID-19. The type of research used is descriptive analysis, with a single variable without looking for a relationship. The research population was all people of Tangkerang Timur Village, Tenayan Raya Subdistrict, Pekanbaru with a sample of 200 people, where the technique used was “Purpossive sampling for 2 weeks with a questionnaire research instrument conducted by visiting the community by applying health protocols. The results of the research analyzed showed that the majority of respondents' knowledge was good 91%, the majority had good attitudes at 88% and the majority had good behavior, namely 71.5%. The conclusion of this research is that people's knowledge, attitudes and behavior are good.